Lean Six Sigma Case Studies in the Healthcare Enterprise - Furterer, Sandra L. (Springer London : Imprint: Springer, 2014)
This book provides a detailed description of how to apply Lean Six Sigma in the health care industry, with a special emphasis on process improvement and operations management in hospitals.  The book begins with a description of the Enterprise Performance Excellence (EPE) improvement methodology developed by the author that links several methodologies including systems thinking, theory of constraints, Lean and Six Sigma to provide an enterprise-wide prioritization and value-chain view of health care. The EPE methodology helps to improve flow at the macro or value-chain level, and then identifies Lean Six Sigma detailed improvements that can further improve processes within the value-chain.  The book also provides real-world health care applications of the EPE and Lean Six Sigma methodologies that showed significant results on throughput, capacity, operational and financial performance. The Enterprise Performance Excellence methodology is described, and also the Six Sigma DMAIC (Define-Measure-Analyze-Improve-Control) problem solving approach which is used to solve problems for health care processes as they are applied to real world cases.  The case studies include a wide variety of processes and problems including:  emergency department throughput improvement; operating room turnaround; operating room organization; CT imaging diagnostic test reduction in an emergency department; linen process improvement; implementing sepsis protocols in an emergency department; critical success factors of an enterprise performance excellence program.